A retrospective study of multimodal analgesic treatment after laparoscopic appendectomy in children. Issue 12 (25th September 2013) - Liu, Yang; Seipel, Catherine; Lopez, Monica E.; Nuchtern, Jed G.; Brandt, Mary L.; Fallon, Sara C.; Manyang, Peter A.; Tjia, Imelda M.; Baijal, Rahul G.; Watcha, Mehernoor F.
Summary: Background: Laparoscopic appendectomy is a common emergency pediatric surgery procedure accompanied by substantial pain (pain scores >4 for >60% of the time) in 33% of these patients. We introduced a bundle of pain management interventions including local anesthetic infiltration at the incision site, intravenous (IV) opioids by patient‐controlled analgesia (PCA), and scheduled doses of IV ketorolac and oral acetaminophen/hydrocodone. Objectives: To evaluate the effect of these pain management interventions on pain control after laparoscopic appendectomy. Methods: We retrospectively studied pain in 206 children above 7 years of age undergoing laparoscopic appendectomy from December 2011 to February 2012 at our institution. We extracted data on patient demographics, duration of anesthesia and surgery, intraoperative opioids, local anesthetic infiltration, surgical procedure reports, along with pain scores, postoperative PCA use, and opioid‐related complications and hospital stays. Patients were divided into two groups – simple appendicitis without peritonitis and appendicitis with generalized peritonitis. Results: The incidence of substantial pain when the multimodal regimen was used was 12%, which is significantly lower than earlier reports (Fisher's exact test P  < 0.001). Patients with generalized peritonitis experienced more pain, consumed more opioids, had more unmet PCA demands, and a higher incidence of respiratory depression compared with those with simple appendicitis. Conclusion: The multimodal regimen of local anesthetic infiltration, opioid by PCA, NSAIDs, and oral acetaminophen/hydrocodone reduced the incidence of substantial pain. Additional studies are required to identify subgroups of patients with minimal opioid requirements who can benefit from modifications of this regimen.